Labor Productivity and Real Exchange Rate : The Balassa-Samuelson Disconnect in the former Yugoslav Republic of Macedonia - Loko, Boileau; Tuladhar, Anita (Washington, D.C. : International Monetary Fund, 2005)
This paper seeks to investigate the transmission mechanisms linking productivity to the real exchange rate in the former Yugoslav Republic of Macedonia. At first glance, the stylized facts-low labor productivity growth and a trend real depreciation-suggest that a Balassa- Samuelson effect is in play. We find that the relationship between the two is not a result of the traditional Balassa-Samuelson effect. Instead, the depreciation of the real exchange rate reflects mainly the behavior of prices in the tradable sector. We argue that the depreciating real exchange rate may reflect a prolonged transition associated with slow technological growth and the low quality of the country's tradable-goods basket.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet